PENTINGNYA PENDIDIKAN KARAKTER SEJAK DINI UNTUK MENYELAMATKAN GENERASI - Pranada Pane; Intan Suriyanti; Triades Sidabutar (JURNAL IMPARTA, 2024)
The term character education is two words that have an important role in human life, whoever is big or small, old and young need it. When these two words are combined, they will provide a deeper understanding and are also expected to bring change in human life. Education is an effort that humans do intentionally to get or discover something new which of course further complements human knowledge. Character is a form of action or action carried out by humans and it can be seen from the results of these human actions if the action gives birth to a form of kindness then it will be judged that the person's character is good but if the human action does not produce something good then the human it will have a value that is not good and can be said to have a bad character. Children are the hope of the family and can even be the hope of the nation so that with all efforts the family will make it so that their children have a good character and attitude. So by teaching character education from an early age it will bring children to good deeds as well so that every child is protected from actions or actions that can harm themselves or even others. In this way, children who are the next generation will be saved from being trapped in this world by equipping them with character education from an early age